2022
DOI: 10.1021/acssuschemeng.2c04230
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Polycarbonates by N-Heterocyclic Carbene-Mediated Ring-Expansion Polymerization and Their Selective Depolymerization to Monomers

Abstract: Cyclic polymers exhibit physical properties that are distinct from their linear analogues. However, syntheses of cyclic polymers from macrocyclic structures with chemical recycling to achieve "ring-to-ring" transformations with high selectivities and yields remain a challenge. This is because regeneration of macrocyclic monomers through a ring-closing strategy without using chemical auxiliaries is not thermodynamically favored. Therefore, in this study, we reported the syntheses of an array of cyclic polycarbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 102 publications
0
7
0
Order By: Relevance
“…The initiation of the copolymerization involves the nucleophilic attack on the carbonyl carbon of the comonomers (VL or 3EG) by iPr-NHC, yielding a tetrahedral intermediate (Int1 VL or Int1 3EG ; Figure S10). 51,67 The calculation revealed that the nucleophilic addition to VL required relatively higher activation energy compared with that to 3EG (iPr-NHC/3EG; ΔG ‡ = 16.52 vs 9.60 kcal mol −1 ), while Int1 VL was thermodynamically favored over Int1 3EG (−10.17 vs −9.62 kcal mol −1 ), indicating that Int1 generated from the interaction between NHC and comonomers was the thermodynamically controlled product. The copolymerization of 3EG exhibited slow kinetics, and the propagation in the ZROP of 3EG was previously reported to be the rate-determining step; 50 4).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The initiation of the copolymerization involves the nucleophilic attack on the carbonyl carbon of the comonomers (VL or 3EG) by iPr-NHC, yielding a tetrahedral intermediate (Int1 VL or Int1 3EG ; Figure S10). 51,67 The calculation revealed that the nucleophilic addition to VL required relatively higher activation energy compared with that to 3EG (iPr-NHC/3EG; ΔG ‡ = 16.52 vs 9.60 kcal mol −1 ), while Int1 VL was thermodynamically favored over Int1 3EG (−10.17 vs −9.62 kcal mol −1 ), indicating that Int1 generated from the interaction between NHC and comonomers was the thermodynamically controlled product. The copolymerization of 3EG exhibited slow kinetics, and the propagation in the ZROP of 3EG was previously reported to be the rate-determining step; 50 4).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The short average block lengths of the copolymer could stem from a chain transfer reaction induced by the high catalytic activity of Me-NHC . We previously reported that bulky substituents of NHC, e.g., diisopropyl NHC ( i Pr-NHC ), resulted in low catalytic activity because the interaction between the NHC and MC was sterically hindered . Therefore, to mitigate the chain transfer reaction and subsequently obtain a cyclic block copolymer, i Pr-NHC was employed for ZcROP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ring structures of attained MCs were associated with little to no ring strains, thus leading to entropy-driven ROP of MCs. 27,28 We hypothesize that the thermodynamics of ROP might be altered to be enthalpy-driven through constraining MCs by the supramolecular interaction with auxiliary, thus increasing the ring strain and ΔH p . To this end, inspired by the electrostatic interaction between the crown ether and an alkali cation (M + ) 29−31 yielding a supramolecular complex to alter the ring strain of crown ether, 32,33 imitate crown ether was designed, aiming to verify our hypothesis that the thermodynamics of ROP of 4EGMC can be modulated by an auxiliary.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Ample methods exist that join polymer chain ends together in processes collectively coined post-polymerization modifications. [1][2][3][4] These coupling reactions remain attractive because they offer the possibility of transforming linear, often easily accessible, polymer chains into new shapes, such as cycles [5][6][7][8] and star polymers, [9][10][11] or new, predetermined sizes in the case of dimerization. [12][13][14][15] In general, synthetic methods rely on modification of the polymer chain ends to useful functional groups that are amenable to participation in "click" reactions, 3,13,[16][17][18][19][20] Diels-Alder cycloadditions, [21][22][23] and esterification reactions, [24][25][26] as examples.…”
Section: Introductionmentioning
confidence: 99%